A "specific perspective" from a "Performance Studies International" voice. An interview with Maaike Bleeker (Mantichora. Italian Journal of Performance Studies, 2020)
Performance Studies, as an academic discipline, was born in the United States, but nowadays it seems not to be only an American field of research. What does Performance Studies look like from a European perspective? This interview with Maaike Bleeker, the current President of the PSi (Performance Studies International), focuses on what international, intercultural and interdisciplinary actually mean in relation to Performance Studies. Here Maiike Bleeker stresses the idea of how powerful Performance Studies becomes when it embraces all the different traditions and the specificities that constitute it